Retrospective Evaluation of Prolene Suture Complications in the Cartilage-Sparing techniques of otoplasty Procedure - Alshehri, Ali Abdullah (Journal of Neonatal Surgery, 2025)
Background: Otoplasty, a cosmetic surgery aimed at correcting prominent ears, is influenced by the choice of suture material. Prolene sutures, which are non-absorbable and durable, are commonly used in otoplasty techniques. This study aims to investigate the complication rates associated with Prolene sutures when using the Cartilage-Sparing techniques. Methods: This retrospective study focuses on data retrieved from Najran University Hospital between 2023 and 2024. The inclusion criteria included patients aged 5 years and above, with a minimum 3-month follow-up, who underwent otoplasty for prominent ears using Cartilage-Sparing techniques with Prolene suture. Data on demographic and clinical characteristics were collected. Statistical analysis was performed using descriptive statistics and chi-square tests, with a p-value of <0.05 considered statistically significant. Results: Among the 34 participants (mean age 16.53 ± 11.31 years), there were 9 females (26.5%) and 25 males (73.5%). The mean follow-up duration was 10.38 ± 22.9 months. Of the participants, 94.1% had no complications, while 2.9% experienced hematoma, and 2.9% had suture extrusion. No significant associations were found with age, sex and laterality. However, follow-up duration showed a significant association with complications (p = 0.016). Conclusions: Prolene sutures demonstrated minimal complications in otoplasty using the Cartilage-Sparing techniques. Further prospective studies with larger sample sizes and extended follow-up are recommended to confirm these results and assess long-term outcomes.